Accumulation of N and P in the Legume Lespedeza davurica in Controlled Mixtures with the Grass Bothriochloa ischaemum under Varying Water and Fertilization Conditions - Xu, Bingcheng; Xu, Weizhou; Wang, Zhi; Chen, Zhifei; Palta, Jairo A.; Chen, Yinglong (Frontiers in Plant Science, 2018)
Water and fertilizers affect the nitrogen (N) and phosphorus (P) acquisition and allocation among organs in dominant species in natural vegetation on the semiarid Loess Plateau. This study aimed to clarify the N and P accumulation and N:P ratio at organ and plant level of a local legume species mixed with a grass species under varying water and fertilizer supplies, and thus to fully understand the requirements and balance of nutrient elements in response to growth conditions change of native species. The N and P concentration in the organ (leaf, stem and root) and plant level of Lespedeza davurica (C3 legume), were examined when intercropped with Bothriochloa ischaemum (C4 grass). The two species were grown outdoors in pots under 80, 60 and 40% of soil water field capacity (FC), -NP, +N, +P and +NP supply and the grass:legume mixture ratios of 2:10, 4:8, 6:6, 8:4, 10:2, and 12:0. The three set of treatments were under a randomized complete block design. Intercropping with B. ischaemum did not affect N concentrations in leaf, stem and root of L .davurica, but reduced P concentration in each organ under P fertilization. Only leaf N concentration in L. davurica showed decreasing trend as soil water content decreased under all fertilization and mixture proportion treatments. Stems had the lowest, while roots had the highest N and P concentration. As the mixture proportion of L. davurica decreased under P fertilization, P concentration in leaf and root also decreased. The N concentration in L. davurica at the whole plant level was 11.1-17.2%. P fertilization improved P concentration, while decreased N:P ratio in L. davurica. The N:P ratios were less than 14.0 under +P and +NP treatments. Our results implied that exogenous N and P fertilizer application may change the N:P stoichiometry and influence the balance between nutrients and organs of native dominant species in natural grassland, and P element should be paid more attention when considering rehabilitating degraded grassland via fertilization application in semiarid Loess Plateau region.